Universal health coverage evolution, ongoing trend, and future challenge: A conceptual and historical policy review - Chhabi Lal Ranabhat; Chhabi Lal Ranabhat; Shambhu Prasad Acharya; Chiranjivi Adhikari; Chiranjivi Adhikari; Chun-Bae Kim (Frontiers Media S.A., 2023)
The goal of universal health coverage (UHC) from the United Nations (UN) has metamorphized from its early phase of primary health care (PHC) to the recent sustainable development goal (SDG). In this context, we aimed to document theoretical and philosophical efforts, historical analysis, financial and political aspects in various eras, and an assessment of coverage during those eras in relation to UHC in a global scenario. Searching with broad keywords circumadjacent to UHC with scope and inter-disciplinary linkages in conceptual analysis, we further narrated the review with the historical development of UHC in different time periods. We proposed, chronologically, these frames as eras of PHC, the millennium development goal (MDG), and the ongoing sustainable development goal (SDG). Literature showed that modern healthcare access and coverage were in extension stages during the PHC era flagshipped with "health for all (HFA)", prolifically achieving vaccination, communicable disease control, and the use of modern contraceptive methods. Following the PHC era, the MDG era markedly reduced maternal, neonatal, and child mortalities mainly in developing countries. Importantly, UHC has shifted its philosophic stand of HFA to a strategic health insurance and its extension. After 2015, the concept of SDG has evolved. The strategy was further reframed as service and financial assurance. Strategies for further resource allocation, integration of health service with social health protection, human resources for health, strategic community participation, and the challenges of financial securities in some global public health concerns like the public health emergency and travelers' and migrants' health are further discussed. Some policy departures such as global partnership, research collaboration, and experience sharing are broadly discussed for recommendation.